The impact of socio-political and economic environments on private sector participation in energy infrastructure delivery in Ghana - Owusu-Manu, D.; Edwards, D.; Kutin-Mensah, E.; Kilby, A.; Parn, E.; Love, Peter (Emerald Group Publishing Limited, 2017)
© 2017, © Emerald Publishing Limited. Purpose: Investment in power and electricity generation for replacing aging infrastructure with new represents a major challenge for developing countries. This paper therefore aims to examine infrastructure projects’ characteristics and how socio-political and economic investment environments interplay to influence the degree of private sector participation (PPP) in infrastructure delivery in Ghana. Design/methodology/approach: Using World Bank Public-private infrastructure advisory facility (PPIAF) and private participation in infrastructure (PPI) project database data from 1994 to 2013, binary logistic regression was used to: determine the probability of a higher or lower degree of PPP; and examine the significance of factors that are determinants of private investments. Findings: The findings reveal that the private sector is more likely to invest in a higher degree of PPP infrastructure projects through greenfield and concession vehicles as opposed to management and leasing contracts. From the extant literature, drivers of PPP included infrastructure project characteristics and the social–economic–political health of the host country. However, the significance, direction and magnitude of these drivers vary. Originality/value: This paper identifies investment drivers to PPP advisors and project managers and seeks to engender discussion among government policymakers responsible for promoting and managing PPP projects. Direction for future work seeks to explore competitive routes to infrastructure debt and equity finance options that finance energy projects.